Analisis Faktor-Faktor Yang Mempengaruhi Audit Delay - Nabilla Filka Noviar; I Wayan Teg Teg (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
The purpose of this research is to examine the factor that influence Audit delay, including gender diversity of directors, profitability, and solvability. The population of this reasearch is banking sector companies listed on the Indonesian Stock Exchange for the 2017-2019 period. Samples were tested as many as 14 companies, with total sample as many as 42 by using purposive sampling. Data are collected with secondary data from banking sector companies that listed in Indonesian Stock Exchange. Research hypothesis testing using T test, F test, and multiple regression analysis using SPSS version 26. The results show that gender diversity of directors, profitability, and solvability have no effect on audit delay on banking sector companies that are listed in Indonesia Stock Exchange for the 2017-2019 period. Keyword: Audit Delay, Gender Diversity of Directors, Profitability, Solvability.